Data augmentation using rotation and shifting - Muhammad Haziq Bin Mornin (Nanyang Technological University, 2024)
In recent times, the usage of Deep Learning has been on the rise in the medical industry. It helps automate many different aspects of the Medical Field and there is still room for improvement in the different aspects. For this project, it will focus on the use of deep learning for image classification of chest X-ray (CXR) scans of the human body for diseases. The usage of Augmentation in supervised learning has been shown to improve the efficiency of the deep learning model.